Analyzing future applications of AI, sensors, and robotics in society - Musiolik, Thomas Heinrich 1980-; Cheok, Adrian David (A volume in the Advances in computational intelligence and robotics (ACIR) book series, 2021)
"This book explores the future challenges and hidden potentials of the application of artificial intelligence, sensors, and robotics in society" - Provided by publisher